Blast from the past: constraining progenitor models of SN 1972E. Issue 3 (20th September 2021) - Do, Aaron; Shappee, Benjamin J; De Cuyper, Jean-Pierre; Tonry, John L; Hunt, Cynthia; Schweizer, François; Phillips, Mark M; Burns, Christopher R; Beaton, Rachael; Hainaut, Olivier
ABSTRACT: We present a novel technique to study Type Ia supernovae (SNe Ia) by constraining surviving companions of historical extragalactic SN by combining archival photographic plates and Hubble Space Telescope ( HST ) imaging. We demonstrate this technique for Supernova 1972E, the nearest known SN Ia in 125 yr. Some models of SNe Ia describe a white dwarf with a non-degenerate companion that donates enough mass to trigger thermonuclear detonation. Hydrodynamic simulations and stellar evolution models show that these donor stars will survive the explosion, and show increased luminosity for at least a 1000 yr. Thus, late-time observations of the exact location of a supernova can constrain the presence of a surviving donor star and progenitor models. We find the explosion site of SN 1972E by analysing 17 digitized photographic plates taken with the European Southern Observatory 1-m Schmidt and 1 plate taken with the Cerro Tololo Inter-American Observatory 1.5-m telescope. Using the Gaia eDR3 catalogue to determine Supernova 1972E's location yields: α = 13 h 39 m 52_.^s 708 ± 0_.^s 004 and δ = −31°40'9_.^′′ 00 ± 0_.^′′ 04 (ICRS). In 2005, HST /ACS imaged the host galaxy of SN 1972E with the F 435 W, F 555 W, and F 814 W filters covering the explosion site. The nearest detected source is offset by 3.0 times our positional precision, and is inconsistent with the colours expected of a surviving donor star. Thus, the limiting magnitude of the HST observation ( F 555 W > 28 mag) rules out all He star companion models and the most luminous main-sequence companion model currently in the literature. The remaining main-sequence companion models could be tested with a 10 orbit HST exposure in the F 606 W filter.